Characterization of Shale Pore Structure by Multitechnique Combination and Multifractal Analysis and Its Significance. (10th November 2020) - Liu, Dengke; Tian, Tao; Liang, Ruixiang; Yang, Fu; Ye, Feng
Abstract : Understanding pore structure would enable us to obtain a deeper insight into the fluid mechanism in porous media. In this research, multifractal analysis by various experiments is employed to analyze the pore structure and heterogeneity characterization in the source rock in Ordos Basin, China. For this purpose, imaging apparatus, intrusion tests, and nonintrusion methods have been used. The results show that the objective shale reservoir contains complex pore network, and minor pores dominant the pore system. Both intrusion and nonintrusion methods detected pore size distributions show multifractal nature, while the former one demonstrates more heterogeneous features. The pore size distributions acquired by low temperature adsorption and nuclear magnetic resonance have relatively good consistence, indicating that similar pore network detection method may share the same mechanism, and the full-ranged pore size distributions need to be acquired by multitechniques. Chlorite has an obvious impact on the heterogeneity of pore structure in narrow pore size range, while illite and I/S mixed layer influence that in wide range. Kerogen index is the fundamental indicators of geochemical parameters. With the decrease of averaged small and middle/large pore radius, the heterogeneity of pore structures increase in narrow and wide ranges, respectively. This work employed a comprehensive methodology based on multitechniques and helps to explore how pore networks affect reservoir quality in shale reservoirs.